Factors Related to Incidence of Anemia in Adolescent Girl (INCH : Journal of Infant and Child Healthcare, 2023)
Anemia is a condition where the level of red blood cells or hemoglobin (Hb) is lower than normal due to iron deficiency. The indicator of anemia in adolescent aged 15-17 years is